Sweden : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
Sweden entered the pandemic with substantial buffers and suffered a relatively shallow recession in 2020. The decline in output was moderated by substantial income and liquidity support as well as structural features of the economy. Sweden's initial less stringent containment strategy seems to have altered the timing of the economic fallout, which intensified towards the middle of the year. This fallout has particularly impacted the youth and foreign-born. Economic recovery is projected over the next two years, but uncertainty has increased due to the new strains of the virus and slow vaccination.